2016
DOI: 10.1186/s13017-016-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of extra-peritoneal pelvic packing in hemodynamically unstable pelvic fractures, a Propensity Score Analysis

Abstract: BackgroundAn option for emergency control of pelvic hemorrhage is Extra-peritoneal Pelvic Packing (EPP), which addresses the retroperitoneal source of exsanguination in pelvic fractures. The aim of this study was to demonstrate the efficacy of early EPP in reducing mortality due to hemorrhage from pelvic fractures, and to evaluate the impact of packing on transfusion requirements within the first 24 h and ICU length of stay (ICU-LOS).All data pertaining trauma patients admitted from October 2002 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 32 publications
2
89
1
12
Order By: Relevance
“…Pelvic fractures patterns included APC III (29), LC II (26), LC III (20), APC II (20), LC I (13), vertical shear (14), APC I (4) and CM (2). Of these, 18 patients had open pelvic fractures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvic fractures patterns included APC III (29), LC II (26), LC III (20), APC II (20), LC I (13), vertical shear (14), APC I (4) and CM (2). Of these, 18 patients had open pelvic fractures.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, those who died due to acute hemorrhage in the PPP group had actually undergone angioembolization first only to require packing for ongoing hemorrhage and instability. In a propensity matched, comparative study of hemodynamically unstable pelvic fracture patients, mortality was significantly reduced with PPP compared to no-PPP (20% vs 52%) (29). This cohort of patients was multiply injured, evidenced by an ISS > 40 for both groups and associated injuries in over 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent observational studies confirmed the notion that extraperitoneal pelvic packing is a safe and fast procedure associated with a significantly reduced mortality in hemodynamically unstable patients with pelvic fractures, compared to patients managed by conventional measures without pelvic packing [8991]. …”
Section: Methodsmentioning
confidence: 97%
“…As a counterpart it is important to consider a number of factors that are critical to decision-making. The exclusive use of angioembolization has been associated with a high mortality in patients with bleeding pelvic fractures [118], which was significantly reduced by application of a combined protocol with initial preperitoneal pelvic packing and subsequent (secondary) angioembolization, if indicated [28, 56, 79, 86, 89]. It has been estimated that 85% of pelvic bleeding originates from bone, soft tissues, or major venous structures [2].…”
Section: Methodsmentioning
confidence: 99%